Response of Nesting Lapland Longspurs (Calcarius lapponicus) to Burned Tundra on the Seward Peninsula - Wright, John M. (ARCTIC, 1981)
The response of breeding Lapland longspurs to burned sedge tussock-shrub tundra was studied in 1978 on the Seward Peninsula in an area burned by lightning-ignited fires during 1977. In late May and mid-June 1978, plant standing crop in burned tundra was <5% of standing crop in unburned tundra. Lapland longspurs were less abundant in burned than unburned tundra. An average of 1.4 longspurs/h were recorded in burned tundra, whereas 4.6 longspurs/h were seen in unburned tundra. One longspur nest was found in 5 ha of burned tundra; three were found in 5 ha of unburned tundra. Nest locations in burned and unburned tundra were similar though nests in burned tundra generally had less protective cover. Several factors may be involved in the reduced abundance of Lapland longspurs in burned tundra.Key words: Lapland longspur, burned tundra, Alaska, abundance, nest sites Mots clés: bruant lapon, toundra incendiée, Alaska, abondance, emplacement de nids